2021
DOI: 10.1098/rspb.2020.2810
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal in heterogeneous environments drives population dynamics and control of tsetse flies

Abstract: Spatio-temporally heterogeneous environments may lead to unexpected population dynamics. Knowledge is needed on local properties favouring population resilience at large scale. For pathogen vectors, such as tsetse flies transmitting human and animal African trypanosomosis, this is crucial to target management strategies. We developed a mechanistic spatio-temporal model of the age-structured population dynamics of tsetse flies, parametrized with field and laboratory data. It accounts for density- and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Other results indicated an overall propensity of 0.57 with G. brevipalpis 32 , while 0.63 and 0.41 were obtained with G. austeni 39 . These dissimilarities may be a result of a difference in treatments and environmental conditions as fly behaviour is indeed influenced by these 63 . However, the relative mating index indicates that the irradiated males are still competitive, and the small deficit as compared with non-irradiated male flies can be mitigated in SIT programmes by an increase in the sterile to wild male ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Other results indicated an overall propensity of 0.57 with G. brevipalpis 32 , while 0.63 and 0.41 were obtained with G. austeni 39 . These dissimilarities may be a result of a difference in treatments and environmental conditions as fly behaviour is indeed influenced by these 63 . However, the relative mating index indicates that the irradiated males are still competitive, and the small deficit as compared with non-irradiated male flies can be mitigated in SIT programmes by an increase in the sterile to wild male ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In the Niayes area in Senegal, a recent study applied a spatial-temporal mechanistic model utilizing satellite-derived environmental data and key knowledge about tsetse biology. The findings revealed that only 4% of the land in Niayes is deemed suitable for tsetse occurrence (Cecilia et al, 2021), which is considerably less than the previously predicted suitability based on the continental tsetse distribution maps (Wint, 2003). In Zambia, recent predictions based on maximum-entropy modelling, and a series of satellite-based predictors indicate a decline in the area coverage of Glossina morsitans morsitans and Glossina morsitans centralis by 47% and 29%, respectively, compared to their historical distribution (Muyobela et al, 2023).…”
Section: Predicting Tsetse Fly Habitats and Abundancementioning
confidence: 60%
“…While these maps were updated twenty years ago, they suffer from a coarse resolution (5x5 km), and their accuracy remains uncertain (Wint, 2003). Local studies have indicated significant disparities between these maps and the actual occurrence of the fly (Esterhuizen et al, 2005;Cecilia et al, 2021), highlighting the pressing need for more accurate and fine-scale mapping approaches. This challenge for improved information and fine-scale mapping extends to tsetse abundance, where there are no available continental maps, and local-scale studies focused on quantifying tsetse abundance are scarce.…”
Section: Identification Of Priority Areas For Tsetse Fly Controlmentioning
confidence: 99%
See 1 more Smart Citation